2021
DOI: 10.1186/s12913-021-06409-0
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between satisfaction with mental health services, personal recovery and quality of life among service users with psychosis: a cross-sectional study

Abstract: Background Mental health policy internationally emphasizes patient centredness and personal recovery. This study investigated the relationship between satisfaction with mental health services among service users with psychosis in Norway, and personal recovery, perceived support for personal recovery, and quality of life. Methods Cross-sectional data were collected from 292 service users diagnosed with psychosis from 39 clinical sites across Norway.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The degree of functional limitations (measured with WHODAS 2.0) in the sample was comparable with other study populations with severe mental illness ( 44 , 53 ). In this study, participants indicated the highest degree of functional limitation in the domains participation in society, work , and household , followed by getting along with people .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The degree of functional limitations (measured with WHODAS 2.0) in the sample was comparable with other study populations with severe mental illness ( 44 , 53 ). In this study, participants indicated the highest degree of functional limitation in the domains participation in society, work , and household , followed by getting along with people .…”
Section: Discussionsupporting
confidence: 78%
“…Our study showed that service users across sites were generally satisfied with the support received from their mental health care providers. A recent study from Norway which also used the INSPIRE tool found that service users who experienced higher perceived support for personal recovery from their health care provider are more satisfied with the care they receive ( 53 ). Nevertheless, there is room for improvement across all centers of the project.…”
Section: Discussionmentioning
confidence: 99%
“…The second approach commonly adopted is subjective outcome evaluation based on the client satisfaction approach. In fact, asking the clients and other stakeholders about their perceptions about the program quality and benefits is widely used in social work (Hsieh, 2006 ), education (Butt & Rehman, 2010 ), and allied health professions (Skar-Fröding et al, 2021 ). In the field of SL, educators have commonly used subjective outcome evaluation to understand the views of different stakeholders via the client satisfaction approach in Western (Chen et al, 2015 ; Lee et al, 2018 ; López-Azuaga and Suárez Riveiro, 2018 ) Maccio & Voorhies, 2012 ; Weiss et al, 2016 ; and Chinese studies (Leung et al, 2021 ; Lin & Shek, 2021 ).…”
Section: Conceptual Framework On Evaluationmentioning
confidence: 99%
“…QoL is defined by the World Health Organization as “an individual’s perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns” [ 15 ]. In health science, an increasing amount of importance is given to this concept as it might better represent the recovery processes than solely relying on symptoms [ 16 , 17 , 18 ]. Indeed, improvements in psychiatric symptomatology do not always translate to actual change in an individual’s life, or in their perception of how they experience life [ 19 ].…”
Section: Introductionmentioning
confidence: 99%